Toxicokinetics of silver nanoparticles in soil organisms - Khodaparast, Zahra (2023)
Nanomaterials are already used in many products and still, the global nanotechnology market is growing. A major route of emission of consumed silver nanoparticles (AgNPs) to soil is through sewage sludge applied as fertilizer. Understanding the possible bioaccumulation of nanoparticles (NPs) in soil organisms is urgently needed as part of their risk assessment. Since NPs are thermodynamically unstable, not likely achieving equilibrium, toxicokinetic studies may indicate their bioavailability and potential for bioaccumulation. Considering the expected transformation of all consumed AgNPs to silver sulfide (Ag₂S), and the lack of enough data regarding Ag₂S bioavailability to terrestrial organisms, this thesis aimed to investigate the toxicokinetics in terrestrial organisms of both pristine (with different coating and size) and sulfidized silver nanoparticles. Ag₂S NPs are simulating aged AgNPs passing through wastewater treatment plants (WWTPs). Different test species were used to assess Ag toxicokinetics under a relevant environmental exposure scenario. This thesis is divided into four studies. The first two studies focused on determining Ag uptake in two invertebrates, mealworms Tenebrio molitor (via Lufa 2.2 soil or food) and enchytraeids Enchytraeus crypticus (via three different soils). Next, the uptake kinetics of Ag in T. molitor and isopods Porcellio scaber was investigated in indoor terrestrial mesocosms as a more relevant environmental condition. Finally, the toxicokinetics and distribution of Ag was studied in the plant Brassica rapa. Exposure of T. molitor and E. crypticus displayed different uptake kinetics for different Ag forms, indicating the effect of AgNP form, characteristics and mainly dissolution on its bioavailability. In both invertebrate species, Ag from Ag₂S NPs could be taken up, but it was eliminated faster than Ag from other Ag forms which may be related to the stability of Ag₂S NPs compared to pristine AgNPs. Significant effects of soil properties on the bioavailability and uptake of Ag nanoparticles were observed in E. crypticus exposed to Ag₂S NPs and AgNO₃ through different soils (Dorset, Woburn, and Lufa 2.2), especially in the Dorset soil, which high sand content and low pH caused clustering behavior of the animals. For checking if the results obtained in standard single-species test could predict Ag uptake under more complex but realistic conditions, the uptake kinetics of Ag₂S NPs and AgNO₃ in T. molitor and P. scaber were estimated in indoor mesocosm with multiple species and with rain application. The single-species tests could not predict Ag uptake in mealworms and isopods in exposure systems having higher levels of biological complexity. To determine the uptake kinetics and distribution of Ag during the growth of the plant up to the complete life cycle, seeds of B. rapa were planted in soil spiked with different Ag forms. The accumulation of Ag in B. rapa differed during the plant life cycle and a two-stage two-compartment model was introduced to describe its uptake kinetics. The concentration of Ag taken up in roots 7 days after germination was about 14 and 10 times lower for Ag₂S NPs than for the pristine AgNPs and AgNO₃ exposures, respectively, but the Ag from the Ag₂S NPs was transferred to the shoots faster than for the other Ag forms. Distribution of Ag in plants exposed for up to 42 days after germination to different Ag forms differed: about 50% of the Ag taken up was present in the shoots for Ag₂S NPs and AgNO₃, but only 20% for the pristine 3-8 or 50 nm AgNPs. Although sulfidation processes in WWTPs significantly decreased its bioavailability, investigating different relevant environmental conditions is required as some conditions may lead to unexpected changes in the bioavailability of sulfidized Ag form NPs.